The Chemistry of Confined Spaces - Jiou, Jenny; Chiravuri, Krishnakanth; Gudapati, Aditya; J. Gassensmith, Jeremiah (Current Organic Chemistry, 2014)
The reactivity in the confined spaces of zeolites, metal-organic frameworks, cage compounds and macrocycles differ in many aspects from those conducted in bulk solution. Cases of altered regioselectivity, enhanced stability and accelerated substrate reactivity are presented within the context of non-covalent interactions between host and guest molecules, which define much of supramolecular chemistry, being unique and imparting highly useful properties that are of interest for their intellectual merit as well as their immense commercial value.
Keywords: metal-organic frameworks